2016
DOI: 10.1136/emermed-2016-206044
|View full text |Cite
|
Sign up to set email alerts
|

Variables associated with administration of analgesia, nurse-initiated analgesia and early analgesia in the emergency department

Abstract: Objective To determine the patient and clinical variables associated with administration of any analgesia, nurse-initiated analgesia (NIA, prescribed and administered by a nurse) and early analgesia (within 30 min of presentation). Methods We undertook a retrospective cohort study of patients who presented to a metropolitan ED in Melbourne, Australia, during July and August, 2013. The ED has an established NIA programme. Patients were included if they were aged 18 years or more and presented with a painful com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
5
1
Order By: Relevance
“…The present study found that mean time of the first analgesia was 94.7 minutes which was much higher than studies done in US, Canada, Australia, Iran and Netherlands in which the mean time of analgesia for most setting in ER was 78 minutes [ 7 , 9 , 27 , 40 – 42 ]. Study in Gondar, Ethiopia in trauma and non-trauma patients revealed the mean time to delivery of analgesia was 61 minutes [ 5 ].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The present study found that mean time of the first analgesia was 94.7 minutes which was much higher than studies done in US, Canada, Australia, Iran and Netherlands in which the mean time of analgesia for most setting in ER was 78 minutes [ 7 , 9 , 27 , 40 – 42 ]. Study in Gondar, Ethiopia in trauma and non-trauma patients revealed the mean time to delivery of analgesia was 61 minutes [ 5 ].…”
Section: Discussioncontrasting
confidence: 75%
“…However, the prevalence of patients who received the first analgesia within 30 minutes in this study was only 9.1%. Study in Gondar, Ethiopia in trauma and non-trauma patients also revealed that only 12.3% of patients received analgesia within 30 minutes of ED presentation [ 5 ] A comparable finding (19.2%) was reported from a study done in Australia [ 40 ]. Nevertheless, a higher prevalence (61.3%) than the current study was obtained from another study done in Australia [ 41 ].…”
Section: Discussionsupporting
confidence: 56%
“…Observations will be recorded as field notes to capture understandings of how emergency nurses detect, assess and manage acute pain in critically ill patients in everyday practice [ 52 ]. There are a lack of studies using observation to identify nurse-initiated analgesia, its safety and impact on patient outcomes; most data collection techniques have included survey/questionnaire [ 35 , 39 , 53 ], interview [ 37 , 54 , 55 ] or audits [ 21 , 24 , 36 , 37 , 39 , 56 58 ]. These methods however reflect only reported, not observed actual practice.…”
Section: Methodsmentioning
confidence: 99%
“…However, after these publications, numerous researchers in different settings have conducted studies with results indicating that patients are still at risk of oligoanalgesia (Arendts & Fry, 2006;Daoust, Paquet, Lavigne, Sanogo, & Chauny, 2014;Hwang, Richardson, Harris, & Morrison, 2010;Ko et al, 2016;Platts-Mills et al, 2012). Oligoanalgesia may also occur in the ED setting (Todd et al, 2007); trauma patients' ≥65 years of age are less likely to receive analgesia than younger patients (Quattromani et al, 2015;Taylor et al, 2017). Cognitively impaired patients have an increased risk of undertreated acute pain (Green & Bernoth, 2016;Morrison & Siu, 2000).…”
Section: Oligoanalgesiamentioning
confidence: 99%